“MEASUREMENTS OF RIGHT EAR OF MEDICAL STUDENTS IN UDAIPUR” - Shrivastava Bhavana; Acharya Sunita; Bharambe Vaishaly Kishore; Medatwal Bhupesh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aims and Objectives: This study aimed to determine the normal anthropometric measurements of right external ear in both males and females. Materials and Methods: The study was carried out on 100 medical students at department of anatomy, Pacific Institute of Medical Sciences, Umarda, Udaipur, Rajasthan, with no evidence of external ear deformities. The cross-sectional analytical study consisted of 50 males and 50 females aged 18-25 years. Digital vernier caliper were used to measure the right external ear. Parameters were total ear length and ear width of right side. Observation and results: It were observed that all parameters were significantly higher in males than in females on right external ear. Conclusion: This study provides the mean values of right ear length and width in medical students of PIMS, Udaipur. Results according to genders who participated in the study where both dimensions were higher in male as compared to the female subjects.